Potential antidiabetic drugs of metformin with insulin-enhancing anions [VO2(dipic)]− and [VO2(dipic-OH)]−: Synthesis, characterization and X-ray crystal structure. (14th December 2015) - Ghasemi, Khaled; Ghasemi, Fatemeh; Rezvani, Ali Reza; Graiff, Claudia; Notash, Behrouz
Graphical abstract: The synthesis and characterization of vanadium anionic complexes of a dipicolinic ligand with metformin as counter ion are described. These complexes can be interesting for biochemists in the potential, associative or synergistic antidiabetic effect because of the coexistence of metformin and insulin-enhancing anions [VO2 (dipic)] − and [VO2 (dipic-OH)] − as well as their solubility in water. Abstract: Two new complexes of antidiabetic drug metformin, [HMet][VO2 (dipic)]·H2 O (1 ) and [HMet][VO2 (dipic-OH)]·H2 O (2 ), where H2 dipic = 2, 6-pyridinedicarboxylic acid, H2 dipic-OH = 4-hydroxy-2, 6-pyridine dicarboxylic acid and Met = metformin, were synthesized. These complexes were characterized by elemental analysis, 1 H and 13 C NMR, FTIR, and UV–Vis spectroscopies. Solid-state structures of [HMet][VO2 (dipic)]·H2 O (monoclinic, P 21 / n ) and [HMet][VO2 (dipic-OH)]·H2 O (monoclinic, P 21 / c ) were determined by means of single crystal X-ray diffraction analysis. In these complexes, metformin is monoprotonated and acted as counter ion. These compounds are soluble in water and hydrogen bond interactions stabilize their crystal structures.